Sistem Pakar Deteksi Kerusakan Sepeda Motor dengan Metode Forward Chaining - Douglas Alfrido; Tjatur Kandaga Gautama (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Abstract — Automatic motorcycle has gain a lot of popularity in recent years. Motorcycle users usually didn’t understand technical issues about their vehicle. The purpose of this research is to build a website that could help motorcycle users to detect damage on their motorcycle. The website employs expert system with forward chaining method. Current knowledge base focused on automatic motorcycle machine failure, but can be expanded or changed to another more broad domain context. Users can get insight of what caused the damage and how to fix it.